2012
DOI: 10.4236/psych.2012.39101
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Negative Priming, but Not Inhibition of Return, with Central (Foveal) Displays

Abstract: The view persists that the inhibition of return (IOR) and the spatial negative priming (SNP) phenomena may be produced by a common "orientation inhibition" mechanism (e.g., Christie & Klein, 2001), held to arise during the processing of peripherally delivered (parafoveal) visual events. Both IOR and SNP effects are present when responding to recently to-be-ignored distractor events is delayed. Since an SNP effect has been produced using centrally located distracters (visual angle of about 2.5˚ or less), a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…These results are in line with arguments from other attention paradigms that also support the claim that object location is processed in a different way than object identity (Constantinidis & Steinmetz, 2005;Johnston & Pashler, 1990;Lamy & Tsal, 2000;Soto & Blanco, 2004). On top of that, there is an ongoing debate over whether the spatial NP effect in vision in fact reflects processes that lead to inhibition of return (IOR; e.g., Buckolz, Fitzgeorge, & Knowles, 2012;Christie & Klein, 2001;Milliken, Tipper, Houghton & Lupianez, 2000) and thus should be separated from identity NP effects altogether.…”
Section: Np In Different Modalitiessupporting
confidence: 67%
“…These results are in line with arguments from other attention paradigms that also support the claim that object location is processed in a different way than object identity (Constantinidis & Steinmetz, 2005;Johnston & Pashler, 1990;Lamy & Tsal, 2000;Soto & Blanco, 2004). On top of that, there is an ongoing debate over whether the spatial NP effect in vision in fact reflects processes that lead to inhibition of return (IOR; e.g., Buckolz, Fitzgeorge, & Knowles, 2012;Christie & Klein, 2001;Milliken, Tipper, Houghton & Lupianez, 2000) and thus should be separated from identity NP effects altogether.…”
Section: Np In Different Modalitiessupporting
confidence: 67%
“…The automated nature of location processing is further indicated by the fact that it takes place even when location discrimination is not needed to perform the task (e.g., on IOR tasks [Mulckhuyse & Theeuwes, 2010] or on Simon tasks [Hommel, 1993]). The utility of such information was illustrated by Buckolz, Fitzgeorge, and Knowles (2011), who found no inhibitory aftereffects in a one-response task using central locations. They claimed that this absence did not result because location discrimination had not occurred; they noted that it took place automatically, in spite of task demands that did not require it.…”
Section: Same-hand Competitionsmentioning
confidence: 99%
“…One study that did report this comparison found early posterior components that were similar for IR and AR trials (Gibbons et al, 2006). These researchers concluded that the mechanisms responsible for inhibition of return also contribute to locationbased negative priming (see also Christie & Klein, 2001;Houghton & Tipper, 1994;Milliken et al, 2000; but see Buckolz et al, 2012). Thus, as with identity-based negative priming, additional work is needed to clarify whether there are early components that are uniquely related to IR effects, rather than shared with AR effects.…”
Section: Negative Priming: Meeting the Multiple Process Challengementioning
confidence: 97%